2016
DOI: 10.1186/s11671-016-1376-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in Transitional Metal-Doped MoS2 Monolayer

Abstract: Manipulating electronic and magnetic properties of two-dimensional (2D) transitional-metal dichalcogenides (TMDs) MX2 by doping has raised a lot of attention recently. By performing the first-principles calculations, we have investigated the structural, electronic, and magnetic properties of transitional metal (TM)-doped MoS2 at low and high impurity concentrations. Our calculation result indicates that the five elements of V-, Mn-, Fe-, Co-, and Cu-doped monolayer MoS2 at low impurity concentration all give r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 42 publications
7
89
0
Order By: Relevance
“…Direct adsorption of metal atoms on the surfaces of TMDs and other 2D materials would in general face the same problem as graphene. Due to inertness of the surfaces, metal dopants may cluster together . However, compared to graphene, there are more possible adsorption sites on 2D materials such as TMDs and phosphorene (see Figure ).…”
Section: Spin Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct adsorption of metal atoms on the surfaces of TMDs and other 2D materials would in general face the same problem as graphene. Due to inertness of the surfaces, metal dopants may cluster together . However, compared to graphene, there are more possible adsorption sites on 2D materials such as TMDs and phosphorene (see Figure ).…”
Section: Spin Generationmentioning
confidence: 99%
“…Similar to graphene, vacancies and other point defects in 2D materials can anchor metals on their surfaces and reduce the diffusivity and formation of metal clusters . Magnetic properties of TM‐doped MoS 2 have been investigated in many first‐principles studies which consistently predicted that Mn‐, Fe‐, and Co‐doped MoS 2 are magnetic . A comprehensive first‐principles study of TM‐doped MoS 2 was carried out by Cheng et al In addition to the above TM atoms, they found that Zn‐, Cd‐, and Hg‐doped monolayer MoS 2 are magnetic, while for the other dopants in the VIIB to IIB groups magnetism is suppressed by Jahn‐Teller distortions.…”
Section: Spin Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, inducing spin polarization by impurity doping in non‐magnetic semiconducting materials has proven to be an effective method as compared to the other methods such as morphology fabrications, external strains, and adsorption . For example, it has been found that the transition‐metal doping of Cr, Mn, Fe, Co, Cr, Zn, Cd, Hg can effectively induce magnetic ground states in MoS 2 and WS 2 . These investigations have realized that doping significantly alters the electronic and magnetic properties to extend the applications of 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] Zhou et al conrmed that Mn, Fe, Co, Ni, Cu and Zn substitutions can induce magnetism in the MoS 2 sheet using the rst principles calculation. 30 Li et al provided experimentally that Co atoms mainly distribute at the edge of MoS 2 nanosheets, forms hexagonal lm, and exhibit halfmetallic behavior.…”
Section: -22mentioning
confidence: 99%